PEMBROLIZUMAB IN THE TREATMENT OF METASTATIC MELANOMA - I. V. SAMOILENKO; L. V. DEMIDOV (Медицинский совет, 2017)
Currently in Russia drugs a new class - immunological synapse modulators (ISM) – appear, the most effective among which are PD-1 blockers. Pembrolizumab is an effective antineoplastic drug, which is a monoclonal antibody blocking the PD-1 signaling molecule on cytotoxic lymphocytes, inhibiting the immune response. Pembrolizumab can be used successfully in the first and subsequent lines of treatment of metastatic melanoma regardless of the presence of activating mutations in the BRAF gene and other molecular markers. Recommended mode of application at the present time is 2 mg/kg intravenously every 3 weeks long before the development of intolerance or overt disease progression. In the present review information is systemized on the effectiveness and safety of using pembrolizumab in patients with metastatic melanoma, is given in a variety of clinical trials and retrospective observations.